Interaction between soluble Aβ‐(1–40) monomer and Aβ‐(1–42) fibrils probed by paramagnetic relaxation enhancement. Issue 6 (15th February 2013) - Yamaguchi, Takahiro; Matsuzaki, Katsumi; Hoshino, Masaru
Abstract : A beta‐(1–42) and A beta‐(1–40) bind by nuclear magnetic resonance (View interaction) Abstract : ► The growth of Aβ‐(1–40) fibrils from Aβ‐(1–42) seeds exhibited a lag phase. ► The Aβ‐(1–40) monomer and Aβ‐(1–42) seed interacted via their C‐terminal region. ► The N‐terminal part of the molecule did not contributed to the interaction.